2013
DOI: 10.5897/ajpp12.944
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, anti-cholinesterase and antibacterial activities of the bark extracts of Garcinia hombroniana

Abstract: This study reports an antioxidant, anti-cholinesterase, antibacterial activities and total flavonoids content of different extracts (water, methanol, ethyl acetate, dichloromethane and n-hexane) of the bark of Garcinia hombroniana. The antioxidant activity was evaluated using radical scavenging of 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), ferric reducing antioxidant power (FRAP) and Folin Ciocalteu assay (FCA). Ethyl acetate extract showed the highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…To date, there are more than fifty xanthones isolated from G. mangostana [15][16] and thirteen xanthones have been isolated from G. hombroniana. [13][14][17][18][19] Xanthones have been widely reported to exhibit diverse pharmacological activities, such as antioxidant, antifungal, antibacterial, anti-inflammatory, antihistamine and antiviral activities. 15,20 Antioxidative properties exhibited by xanthones, benzophenones and flavonoids would correspond to the high FRS and FRP in G. mangostana and G. hombroniana.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are more than fifty xanthones isolated from G. mangostana [15][16] and thirteen xanthones have been isolated from G. hombroniana. [13][14][17][18][19] Xanthones have been widely reported to exhibit diverse pharmacological activities, such as antioxidant, antifungal, antibacterial, anti-inflammatory, antihistamine and antiviral activities. 15,20 Antioxidative properties exhibited by xanthones, benzophenones and flavonoids would correspond to the high FRS and FRP in G. mangostana and G. hombroniana.…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemical studies have been extensively carried out on different parts of G. celebica resulting in the identification of various classes of secondary metabolites including benzophenones, triterpenoids, xanthones, flavonoids and bisflavonoids. In addition to these classes, sesquiterpenoids, sesquiterpenes, depisidones, sterols, benzoic acid derivatives, coumaric acids, fatty acids and ionone-derived glycosides also enrich the diversity of the phytochemistry of G. celebica [ 13 , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] ]. To date, as many as 100 compounds have been identified in this review according to our search.…”
Section: Phytochemical Constituentsmentioning
confidence: 99%
“…People familiar with G. hombroniana Pierre as mangosteen family of plants that are ornamental plants, food crops, and as a traditional medicine for itchy. 2 Previous research has been conducted on the bark of G. hombroniana Pierre which showed that the ethyl acetate extract had the highest content of flavonoid and antioxidant activity EC 50 values obtained by FRAP method is 5579.8 ± 117.7 mol TE (Trolox Equivalent)/g. 2 Garcinia hombroniana Pierre leaves extract have been known to contain flavonoid, 3 but it has not been known yet for its antioxidant activity and inhibition of lipoxygenase activity.…”
Section: Introductionmentioning
confidence: 99%
“…2 Previous research has been conducted on the bark of G. hombroniana Pierre which showed that the ethyl acetate extract had the highest content of flavonoid and antioxidant activity EC 50 values obtained by FRAP method is 5579.8 ± 117.7 mol TE (Trolox Equivalent)/g. 2 Garcinia hombroniana Pierre leaves extract have been known to contain flavonoid, 3 but it has not been known yet for its antioxidant activity and inhibition of lipoxygenase activity. This study aims to determine antioxidant activity tested by using FRAP (Ferric Reducing Antioxidant Power) method and inhibition of lipoxygenase activity of G. hombroniana leaves extract.…”
Section: Introductionmentioning
confidence: 99%